Local hippocampal fast gamma rhythms precede brain-wide hyperemic patterns during spontaneous rodent REM sleep - Antoine Bergel (Nature Portfolio, 2018)
Neural activity during REM sleep is similar to the waking state. Here, the authors measure blood volume with neurofunctional ultrasound imaging together with hippocampal neural activity during REM sleep and report that fast gamma oscillations are coupled to a brain-wide upregulation of vascular flow.